Soft Power of Military Power - V.M. Rusakov (Дискурс Пи, 2017)
The content of the concept of "soft power" is sufficiently investigated in modern literature. Various "soft power" measurement systems have been developed. But there is one more direction - "soft power" of the military power. The article raises the problem and defines the content of "soft power of military power" on the example of comparison of the applied practices in the armed forces of Russia and its likely opponents.